PENERAPAN PRINSIP PEMBELAJARAN MENDALAM DALAM MENINGKATKAN KEMAMPUAN BERKESADARAN DALAM PRAKTEK PEMBELAJARAN - Ayuni, Ayuni; Muhammad Zaini Ilmi; Fidya Aisyah Asyifa; Nur Istiqomah; Ahmad Suriansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article explores the application of deep learning principles to strengthen students’ mindfulness in instructional settings. The study addresses the problem of limited learner awareness and the dominance of surface-level learning in classroom practices. The purpose is to examine how conceptual understanding, critical thinking, and reflective engagement within deep learning can enhance students’ focused attention, emotional regulation, and conscious awareness. Using a literature review method, this article synthesizes theoretical perspectives and previous research to analyze the relationship between deep learning and mindfulness. The findings indicate that deep learning environments foster reflective thinking, intentional engagement, and meaningful knowledge integration, which collectively support the development of mindfulness skills. The review concludes that implementing deep learning principles can significantly improve both cognitive and affective aspects of learning, leading to more conscious and holistic learning experiences.